Application of inulin in cheese as prebiotic, fat replacer and texturizer: A review. (30th March 2015) - Karimi, Reza; Azizi, Mohammad Hossein; Ghasemlou, Mehran; Vaziri, Moharam
Highlights: This paper gives an overview of prebiotic effect of inulin in cheese. Application of inulin as fat replacer has been reviewed. The effect of inulin on texture of various cheeses has been overviewed. Application of inulin is of great interest in development of symbiotic cheese. Abstract: Inulin is a food ingredient that belongs to a class of carbohydrates known as fructans. Nutritionally it has functional properties and health-promoting effects that include reduced calorie value, dietary fiber and prebiotic effects. Inulin is increasingly used in industrially processed dairy and non-dairy products because it is a bulking agent for use in fat replacement, textural modification and organoleptic improvement. Addition of inulin to different kinds of cheese can be beneficial in the manufacture of a reduced- or low-fat, texturized, symbiotic product. This paper gives an overview of some aspects of the microstructural, textural, rheological, prebiotic and sensorial effects of inulin incorporated in cheese as fat replacer, prebiotic and texture modifier.